Analisis Pengaruh PDRB, Pendapatan Per Kapita Dan Investasi Terhadap Indeks Pembangunan Manusia di Kabupaten Mimika - Leisubun, Julia Beby; Pangala, Nopita Lisa; Ialuhun, Pritty; Arapi, Rahmat (ProBisnis : Jurnal Manajemen, 2024)
This study aims to analyze the influence of Gross Regional Domestic Product (GDP), Per Capita Income, and Investment on the Human Development Index (HDI) in Mimika Regency. The method used is an associative method with a type of quantitative data sourced from secondary data obtained from the Central Statistics Agency (BPS) of Mimika Regency during the 2014-2023 period. The data were analyzed using multiple linear regression to determine the relationship between independent and dependent variables. The results of the analysis show that the GDP has a negative and significant influence on HDI, showing that economic growth is not accompanied by an improvement in the quality of life or human development. In contrast, Per Capita Income and Investment had a positive and significant influence on HDI, suggesting that increased per capita income and investment contributed to better access to education and health services, as well as an overall improvement in living standards. These findings indicate the need for policies that support a fairer distribution of income and increased investment in the education